Tamoxifen down-regulates CaMKII messenger RNA levels in normal human breast tissue - Silva, I. D. C. Guerreiro da; Dias-Netto, E.; Villanova, F. E.; Yamamoto, L.; Baracat, E. C.; Lima, G. R.; Gebrim, L. H. (My University, 2004)
Tamoxifen was proven to reduce the incidence of breast cancer by 49% in women at increased risk of the disease in the Breast Cancer Prevention Trial. In order to identify potential candidates to explain the preventive effect induced by tamoxifen on breast cancer, normal breast tissue obtained from 42 fibroadenoma patients, randomly assigned to receive placebo or tamoxifen, was analyzed by the reverse Northern blot and RT-PCR techniques. The cDNA fragments used on Northern blot membranes were generated by the Human Cancer Genome Project funded by the Ludwig Institute for Cancer Research and FAPESP (Fundação de Amparo à Pesquisa do Estado de São Paulo, Brazil). Total RNA was obtained from normal breast tissue from patients with clinical, cytological and ultrasound diagnosis of fibroadenoma. After a 50-day treatment with tamoxifen (10 or 20 mg/day) or placebo, normal breast tissue adjacent to the tumor was collected during lumpectomy with local anesthesia. One differentially expressed gene, Calcium/calmodulin-dependent protein kinase II (CaMKII), was found to be down-regulated during TAM treatment. CaMKII is an ubiquitous serine/threonine protein kinase that has been implicated in the diverse effects of hormones utilizing Ca2+ as a second messenger as well as in c-fos activation. These results indicate that the down-regulation of CaMKII induced by TAM might represent alternative or additional mechanisms of the action of this drug on cell cycle control and response to hormones in normal human breast tissue.
Keywords: Breast Tissue; Ca+2-signalling; CaMKII; Human Cancer Genome Project; Tamoxifen; DNA fragment; hormone; messenger RNA; protein serine threonine kinase; tamoxifen; adult; breast; breast cancer; breast fibroadenoma; calcium signaling; camkII gene; cell cycle; clinical article; clinical trial; controlled clinical trial; controlled study; cytodiagnosis; double blind procedure; down regulation; drug mechanism; echography; female; gene; gene activation; gene expression; genome; human; human cancer genome project; human cell; human tissue; local anesthesia; Northern blotting; nucleotide sequence; oncogene c fos; partial mastectomy; prospective study; randomized controlled trial; reverse transcription polymerase chain reaction; second messenger; Antineoplastic Agents, Hormonal; Blotting, Northern; Breast; Breast Neoplasms; Ca(2+)-Calmodulin Dependent Protein Kinase; Double-Blind Method; Down-Regulation; Female; Fibroadenoma; Humans; Prospective Studies; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger